Made in Nusantara studies in popular music - Adil Johan; Santaella, Mayco A. (Routledge global popular music series., 2021)
"Made in Nusantara serves as a comprehensive introduction to the history, sociology, ethnography and musicology of historical and contemporary popular music in maritime Southeast Asia. Each essay covers major figures, styles, and social contexts of genres of a popular nature in the Nusantara region including Malaysia, Indonesia, Brunei, Singapore, and the Philippines. Through a critical investigation of specific genres and their spaces of performance, production, and consumption, the volume is organized into four thematic areas: 1) issues in Nusantara popular music; 2) history; 3) artistes and genres; and 4) national vs local industries. Written by scholars working in the region, Made in Nusantara brings local perspectives to the history and analysis of popular music and critically considers conceptualisations developed in the West, rendering it as an intriguing read for students and scholars of Popular and Global Music"-- Provided by publisher.